Translation and cross-cultural adaptation to Brazilian culture of a questionnaire to measure perceptions of dental aesthetics - doi: 10.5020/18061230.2010.p316 - Gabriela Eugênio de Sousa Furtado; Maria da Luz Rosário de Sousa; Maria da Luz Rosário de Sousa; Esperanza de Los Angeles Martínez-Mier; Esperanza de Los Angeles Martínez-Mier; Débora Dias da Silva; Débora Dias da Silva; Nádia Deschamps; Nádia Deschamps; Maria Eneide Leitão de Almeida; Maria Eneide Leitão de Almeida (Universidade de Fortaleza, 2012)
Objective: To conduct the translation to Portuguese and the cross-cultural adaptation to Brazilian culture of a questionnaire to evaluate the aesthetic concerns of 12-yr-old children and their parents. Methods: The original questionnaire, which investigates the level of the child´s distress, worry, and smile avoidance in the last two months, was not validated to any other languages but the ones it was originally developed for (English and Spanish). This report had the following design: translation, back-translation, validation by a panel of experts and testing of the final version with 50 pairs of parents/children, using self-report or interview. Results: No relevant discrepancy amongst versions was found; only minor adjustments were made to adapt the questionnaire to the target population´s diverse educational background, and no item from the original questionnaire has been removed. Simple vocabulary and short phrases were used in order to facilitate the application to children and adults in a location in the Northeast and another in Southeastern Brazil. In the pre-testing, Brazilians easily understood the questions. When the questionnaire was self-applied, there was difficult in reading by children, non-response from parents and unanswered items by both groups. Conclusion: The Child's and Parent's Questionnaire about Teeth Appearance was adequately translated into Brazilian Portuguese and adapted to the cultural context of both locations, and it is suggested using it as an interview